Liquid‐Exfoliated Black Phosphorous Nanosheet Thin Films for Flexible Resistive Random Access Memory Applications. (5th February 2016) - Hao, Chunxue; Wen, Fusheng; Xiang, Jianyong; Yuan, Shijun; Yang, Bingchao; Li, Lei; Wang, Wenhong; Zeng, Zhongming; Wang, Limin; Liu, Zhongyuan; Tian, Yongjun
Abstract : Black phosphorous (BP) is a unique layered p‐type semiconducting material. The successful use of BP nanosheets in field‐effect transistors fueled research on BP atomic layers that focuses on, e.g., the exploration of their optical and electronic properties, and promising applications in (opto)electronics. However, BP films are prone to degradation in ambient conditions, which prevents their commercial application. Here, a route to the application of BP films as an environmental stable nonvolatile resistive random access memory is presented. The BP films, which are prepared from exfoliated BP nanosheets in selected solvents, show solvent‐dependent degradation upon ambient exposure, inducing the formation of an amorphous top degraded layer (TDL). The TDL acts as an insulating barrier just below the Al electrode. This property that was only obtained by degradation, confers a bipolar resistive switching behavior with a high ON/OFF current ratio up to 3 × 10 5 and excellent retention ability over 10 5 s to the flexible BP memory devices. The TDL also prevents propagation of degradation further into the film, ensuring excellent memory performance even after three month of ambient exposure. Abstract : Environmental stable nonvolatile resistive random access memory devices are fabricated with liquid‐exfoliated black phosphorous (BP) nanosheets. Exposure to ambient conditions induces an amorphous top degraded layer with insulating properties in BP‐nanosheet‐based film. Resulting BP memory devices exhibit a bipolar resistive switching behavior with a high ON/OFF current ratio up to 3 × 10 5 and an excellent retention ability over 10 5 s.